HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN TUBERCULOSIS (TB) PADA ANAK : THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES WITH TUBERCULOSIS (TB) PREVENTION BEHAVIORS IN CHILDREN - Wirakhmi, Ikit; Iwan Purnawan; Yuli Dwi Hartanto (Intan Husada : Jurnal Ilmiah Keperawatan, 2024)
Background. Tuberculosis (TB) remains a significant public health issue both in Indonesia and internationally, making it one of the targets of sustainable health development goals (SDGs). The proportion of childhood tuberculosis cases in Central Java in 2022 was 19.5%, an increase compared to the 2021 proportion of 11.2%. This indicates that the transmission of tuberculosis cases to children is on the rise. Knowledge and attitudes are essential in promoting healthy behaviors, including efforts to prevent TB.Purpose. To determine the relationship between knowledge and attitudes with tuberculosis (TB) prevention behaviors in children.Methods.. This study is a quantitative correlational research. The study design is a cross-sectional study. The respondents were mothers with toddlers at Posyandu Mugi Slamet in Ledug Village, Kembaran Subdistrict, Banyumas Regency. The sample was taken using accidental sampling techniques, totaling 23 respondents. Data were collected on June 7, 2024. The research instrument used a questionnaire. The analysis used includes univariate and bivariate.Result. The majority had primary education (65.2%) and were unemployed (87%). Most respondents had good knowledge (56.5%), positive attitudes (91.3%), and positive behaviors (95.7%). The correlation between knowledge and behavior was not statistically significant (p = 0.184). A correlation value of 0.184 indicates a very weak positive correlation. The correlation between attitude and behavior was not statistically significant (p = 0.66). A correlation value of 0.752 indicates a strong positive correlation.Conclusion. There is no significant relationship between mothers' knowledge and attitudes with TB prevention behaviors in children.